Assessment and comparison between effectiveness of techniques of improving lactation among postnatal mothers of new born babies - Asrani, Anita; Varghese, Achamma; Sharma, Balkishan; Jain, Anil Kumar (Asian Journal of Medical Sciences, 2018)
Background: Breast milk is a combination of food and medicine tailor made to meet the requirements of the new born, is extremely easy to digest and is therefore the perfect first food for the new born. Aims and Objectives: Authors evaluated 60 postnatal mothers of new born babies to determine the effectiveness of back massage as compared to cumin seeds laddo techniques on improving lactation. Materials and Methods: A quasi experimental study designed among sixty postnatal mothers to observe the effectiveness of methods of improving lactation randomly dived into two groups. Subjects of group 1 received back massage while cumin seed laddoo provided to subjects of group 2. The ethical clearance was obtaines. Data recorded at baseline (pretest) and for three successive days, 1, 2 and 3 post administration (post-test). Results: 83.3% of the post natal mothers of group 1 (n1=30) and 86.7% of group 2 (n2=30) observed without any previous problem in breast feeding. The appearance of stool found to be associated significantly post administration on day 2 (p<0.003) and day 3 (p<0.006) with used techniques. On day 3, 63.3% noticed with good category received back massage against 40.0% administered cumin seed laddo. Mean birth weight of baby (2681.33±260.89 gram) at post-test of group 1 was higher than group 2 (2607.00±402.19 gram). Differences in mean number of nappies wetted, number of feed and time taken by the baby between groups on days 2 and 3 were highly significant (p<0.001). Average total post-test scoring were statistically significant on day 3 (p<0.05). However, back massage was more effective than cumin seed laddo. Conclusion: This study supports the view of improvement in lactation among post natal mother incorporated to good health of new born by administering back massage. In the Indian context, there are many studies carried out on improvement in lactation among post natal mothers but none of the study demonstrated comparison between two lactation techniques. Asian Journal of Medical Sciences Vol.9(1) 2018 41-49